Preliminary Results of Bone Regeneration in Oromaxillomandibular Surgery Using Synthetic Granular Graft. (5th November 2018) - Mazzone, Noemi; Mici, E.; Calvo, A.; Runci, M.; Crimi, S.; Lauritano, F.; Belli, E.
Abstract : Traumatic, neoplastic, inflammatory, or infective dental removal promotes a gradual resorption process of bone which leads to a "nonuse" atrophy of the alveolar ridges. Many techniques allows restoring an appropriate bone thickness, but nowadays the attention is focused on the use of natural or synthetic grafts. Numerous studies have been conducted to develop and test new synthetic materials. In this article, the authors report their experience using a synthetic bone substitute in combination with Platelet Rich Fibrin (PRF). This technique was applied in different zones of the maxillomandibular district. The procedure showed a very satisfying bone regeneration without important complications.